Divorce of Pregnant Women: A Comparative Study Analysis of The Thoughts of The Syāfi’i Mażhab and The Māliki Mażhab - Farih Izzulhaq (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2023)
This article is a comparative study of the thoughts of the Mażhab Syāfi’i and the Mażhab Māliki on the divorce of pregnant women. Mażhab Syāfi’i allows divorces to take place during pregnancy. However, some adherents of mażhab Māliki prohibit divorce from being pregnant. This writing aims to find out the legal istinbat methods used by both. This type of research includes library research with normative approaches and fiqh that is descriptive-analytic to describe the problem of divorce of pregnant women. The results of this study are that the legal istinbaţ method used by mażhab Syāfi’i is the Qur’an, and the Hadith is based on surah Aţ-Ţalāq verse 1 and Hadith from Ibn Umar RA. Otherwise, mażhab Māliki (Al-Qodhi Abu Hasan) uses “qiyas” as the method of istinbaţ his law. Abu Hasan killed a pregnant woman with a man who had menstruated until it was illegal to divorce